150 Administering an appeasing substance to Bos indicus-influenced beef cattle at weaning and feedlot entry. (5th December 2019) - Millican, Allison; Cooke, Reinaldo F; Brandão, Alice; Schumaher, Thiago; Souza, Osvaldo; Castro, Thais; Cappellozza, Bruno
Abstract: Bovine appeasing substance (BAS) is expected to have calming effect in cattle experiencing stressful situations, including weaning and feedlot arrival. In Exp. 1, 186 Bos indicus-influenced calves (73 heifers, 133 bulls) were weaned at 211 ± 1 d of age (d 0). Upon weaning, calves were ranked by sex and body weight (BW), and assigned to receive BAS (Nutricorp, Araras, SP, Brazil; n = 94) or water (CON; n = 92). Treatments (5-mL) were topically applied to the forehead of each animal. Calf BW was recorded and samples of blood and tail-switch hair collected on d 0, 15, and 45. Calves that received BAS had greater (P < 0.01) average daily again (ADG) from d 0 to 15, and BW on d 15 compared with CON. Overall ADG and BW on d 45 were also greater (P < 0.05) in BAS vs. CON. Plasma concentrations of haptoglobin were less (P < 0.01) in BAS vs. CON cattle on d 15, whereas cortisol concentrations in plasma and tail-switch hair did not differ between treatments (P > 0.16). In Exp. 2, 140 B. indicus-influenced bulls (~27 mo of age) were transported from a cow-calf ranch to a commercial feedlot (d -1), and maintained on a single pasture for 24 h. On d 0, bulls were ranked by BW and assigned to receive BAS (n = 70) or CON (n = 70) as in Exp. 1. Bulls receiving BAS had greater (P = 0.04) ADG from d 0 to 15, but less (P < 0.01) ADG from d 15 to 45 compared to CON. No other treatment effects were detected (P > 0.18). Therefore, BAS administration to beef cattle at weaning or feedlot entry had immediate benefits to ADG, which were sustained for 45 d in weaned calves but not in feedlot cattle.